Confirming the Validity of the School-Refusal Assessment Scale—Revised in a Sample of Children With Attention-Deficit/Hyperactivity Disorder - Orm, Stian; Orm, Cathrine; Mebostad, Mette I.; Dechsling, Anders; Nordahl-Hansen, Anders (Frontiers in Psychology, 2022)
Children with developmental disorders, such as Attention-Deficit/Hyperactivity Disorder (ADHD), are at high risk of school-refusal behavior (SRB) compared with their peers. One of the most used scales to assess SRB is the School Refusal Behavior Scale – Revised (SRAS-R). The SRAS-R has demonstrated good psychometric properties when used with the general population of children but recently its validity has been questioned when used with children with developmental disorders. We tested the psychometric properties of the SRAS-R parental reports in 96 children with ADHD (Mage = 12.4; SD = 1.7, 61.5% boys). Results showed good model fit and internal consistency for the original four-factor structure. Three of the factors were strongly correlated, suggesting that SRB among children with ADHD are caused by several factors.